The dose-dependent psychomotor effects of intravenous delta-9-tetrahydrocannabinol (Δ 9 -THC) in humans - Boggs, Douglas L; Cortes-Briones, Jose A; Surti, Toral; Luddy, Christina; Ranganathan, Mohini; Cahill, John D; Sewell, Andrew R; D'Souza, Deepak C; Skosnik, Patrick D (Journal of psychopharmacology (Oxford), 2018)
Binding studies have demonstrated that levels of the cannabinoid receptor type-1 are highest in the basal ganglia and cerebellum, two areas critical for motor control. However, no studies have systematically examined the dose-related effects of intravenous delta-9-tetrahydrocannabinol, the primary cannabinoid receptor type-1 partial agonist in cannabis, on broad domains of psychomotor function in humans. Therefore, three domains of psychomotor function were assessed in former cannabis users (cannabis abstinent for a minimum of three months; n=23) in a three test-day, within-subject, double-blind, randomized, cross-over, and counterbalanced study during which they received intravenous delta-9-tetrahydrocannabinol (placebo, 0.015 mg/kg, and 0.03 mg/kg). Gross motor function was assessed via the Cambridge Neuropsychological Test Automated Battery Motor Screening Task, fine motor control via the Lafayette Instrument Grooved Pegboard task, and motor timing via a Paced Finger-Tapping Task. In addition, the Cambridge Neuropsychological Test Automated Battery Rapid Visual Processing Task was utilized to determine whether delta-9-tetrahydrocannabinol-induced motor deficits were confounded by disruptions in sustained attention. Delta-9-tetrahydrocannabinol resulted in robust dose-dependent deficits in fine motor control (Grooved Pegboard Task) and motor timing (Paced Finger-Tapping Task), while gross motor performance (Motor Screening Task) and sustained attention (Rapid Visual Processing Task) were unimpaired. Interestingly, despite the observed dose-dependent increases in motor impairment and blood levels of delta-9-tetrahydrocannabinol, subjects reported similar levels of intoxication in the two drug conditions. These data suggest that while several domains of motor function are disrupted by delta-9-tetrahydrocannabinol, subjective feelings of intoxication are dissociable from cannabinoid-induced psychomotor effects. Results are discussed in terms of the potential neural mechanisms of delta-9-tetrahydrocannabinol in motor structures.